Kompetencje kluczowe w edukacji dzieci: od deklaracji do realizacji = Key competences in children`s education: from declaration to implementation - Nowak-Łojewska, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The text addresses the concept of key competences. It is not an analysis of what key competences are but of how they are understood and interpreted from various paradigmatic perspectives. The context for the discussion is the paradigm map constructed by Dorota Klus-Stańska, and particular attention is paid here to the so called multiparadigm of didactics. The purpose of the text is not to expose the superiority of some paradigms over others but to indicate how di?erent theoretical context in?uences the understanding and implementation of the concept in practice.
Keywords: kompetencje kluczowe; paradygmaty dydaktyki; świadomość dydaktyczna; re?eksja pedagogiczna; key competences; paradigms of didactics; didactic awareness; pedagogical re?ection